Akupresure untuk Mengatasi Nyeri pada Ibu Hamil Trimester III di Puskesmas Sumowono Semarang - Rahayu, Erna; Putri, Nabila; Susanti, Rini (Prosiding Seminar Nasional dan CFP Kebidanan Universitas Ngudi Waluyo, 2023)
Pain causes a person to experience fear and anxiety that increases stress and experiences drastic physiological changes during pregnancy and anxiety synergize and worsen each other. Acupressure is a type of massage therapy that can stimulate the body to produce endorphins and opioids so as to reduce pain and anxiety. This Community Service activity aims to increase interaction and sharing experiences between participants (pregnant women with pregnant women) and between pregnant women and health workers / midwives and increase understanding, attitudes and behaviors of pregnant women about acupressure, body changes and complaints, pregnancy care, childbirth. Method used by the implementation team seeks to provide more focused knowledge about acupressure in the second and third trimester of pregnant women to overcome pain and discomfort during pregnancy. Results This service activity begins with the stage of identifying or collecting data on the target number of pregnant women, then first a pre-test is carried out to find out the extent of pregnant women's knowledge about acupressure to overcome pain in pregnant women in the second and third trimesters and its benefits. Second, counseling was carried out on acupressure to overcome pain in pregnant women in the second and third trimesters, and a post test was carried out to determine the level of knowledge of pregnant women about acupressure to overcome pain in pregnant women in the second and third trimesters. Third, a demonstration and practice of implementing acupressure to overcome pain in pregnant women in the second and third trimesters was followed by 7 pregnant women in Bumen Village. This devotion showed that there was a level of knowledge of pregnant women about acupressure to treat pain in pregnant women in the second trimester and third trimester after being given counseling increased, namely 7 participants of pregnant women became well informed (70%). Suggestion Pregnant women can do acupressure to overcome pain in pregnant women trimester II and III independently at home. It is necessary to do similar activities in other areas that have not had the opportunity to do this activity to help pregnant women who often experience pain during pregnancy. Abstrak Nyeri menyebabkan seseorang mengalami ketakutan serta kecemasan sehingga meningkatkan stres dan mengalami perubahan fisiologis secara drastis selama  kehamilannya serta kecemasan saling sinergis dan memperburuk antara satu  sama  lainnya. Akupresur merupakan jenis terapi pijat yang dapat menstimulasi tubuh untuk memproduksi hormon endorfin dan opioid sehingga dapat mengurangi rasa sakit dan cemas. Kegiatan Pengabdian Masyarakat ini bertujuan meningkatkan interaksi dan berbagi pengalaman antar peserta (ibu hamil dengan ibu hamil) dan antar ibu hamil dengan petugas kesehatan/bidan dan meningkatkan pemahaman, sikap dan perilaku ibu hamil tentang akupresure, perubahan tubuh dan keluhan, perawatan kehamilan, persalinan. Metode yang digunakan oleh tim pelaksana berupaya memberikan pengetahuan secara lebih fokus tentang akupresure pada ibu hamil trimester II dan trimester III untuk mengatasi nyeri dan ketidaknyaman selama kehamilan. Hasil Kegiatan pengabdian ini diawali dengan tahapan identifikasi atau pendataan jumlah sasaran ibu hamil, selanjutnya pertama dilakukan pre test untuk mengetahui sejauh mana pengetahuan ibu hamil mengenai akupresure untuk mengatasi nyeri pada ibu hamil trimester II dan III serta manfaatnya. Kedua dilakukan penyuluhan mengenai akupresure untuk mengatasi nyeri pada ibu hamil trimester II dan III, dan dilakukan post test untuk mengetahui tingkat pengetahuan ibu hamil tentang akupresure untuk mengatasi nyeri pada ibu hamil trimester II dan III. Ketiga dilakukan demonstrasi dan praktik pelaksanaan akupresure untuk mengatasi nyeri pada ibu hamil trimester II dan III yang di ikuti oleh 7 ibu hamil di desa bumen. Pengabdian ini menunjukkan bahwa terdapat tingkat pengetahuan ibu hamil mengenai akupresure untuk mengaasi nyeri pada ibu hamil trimester II dan trimester III setelah diberikan penyuluhan meningkat yaitu 7 peserta ibu hamil menjadi berpengetahuan baik (70%).